The Essential Oil of Artemisia argyi H.Lév. and Vaniot Attenuates NLRP3 Inflammasome Activation in THP-1 Cells - Chen, Pengxiao; Bai, Qi; Wu, Yanting; Zeng, Qiongzhen; Song, Xiaowei; Guo, Yuying; Zhou, Pengjun; Wang, Yao; Liao, Xiaofeng; Wang, Qiaoli; Ren, Zhe; Wang, Yifei (Frontiers in Pharmacology, 2021)
Artemisia argyi H. Lév. and Vaniot is a traditional medical herb that has been used for a long time in China and other Asian counties. Essential oil is the main active fraction of Artemisia argyi H. Lév. and Vaniot, and its anti-inflammatory potential has been observed in vitro and in vivo. Here, we found that the essential oil of Artemisia argyi H. Lév. and Vaniot (EOAA) inhibited monosodium urate (MSU)- and nigericin-induced NLRP3 inflammasome activation. EOAA suppressed caspase-1 and IL-1β processing and pyroptosis. NF-κB p65 phosphorylation and translocation were also inhibited. In addition, EOAA suppressed nigericin-induced NLRP3 inflammasome activation without blocking ASC oligomerization, suggesting that it may inhibit NLRP3 inflammasome activation by preventing caspase-1 processing. Our study thus indicates that EOAA inhibits NLRP3 inflammasome activation and has therapeutic potential against NLRP3-driven diseases.